ChemInform Abstract: Newly‐Generated Al(OH)3‐Supported Pd Nanoparticles‐Catalyzed Stille and Kumada Coupling Reactions of Diazonium Salts, (Het)aryl Chlorides. Issue 20 (April 2016) - Li, Xing; Zhu, Tingting; Shao, Zhongqi; Li, Yingjun; Chang, Honghong; Gao, Wenchao; Zhang, Yongli; Wei, Wenlong
Abstract: The title reaction features excellent functional group compatibility, moderate to good yields, and feasibility of using heteroaryl chlorides, diazonium salts, and Grignard reagents.